IMPLEMENTASI PENYALAHGUNAAN DISKRESI YANG MELAHIRKAN TANGGUNG JAWAB PIDANA - Mustamu, Julista (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study examines the implementation of abuse of discretion that gives birth to criminal responsibility in the context of Indonesian law. Discretion is an important authority given to government officials to overcome legal vacancies or ambiguities in the administration of government. However, in practice, there are often abuses that cause state losses and have implications for criminal liability. This research uses normative juridical methods with legislative, conceptual, and case approaches. The results of the study show that there is complexity in determining the parameters of the abuse of discretion that can be punished, given the different characteristics between administrative law and criminal law. The inconsistency of the court’s approach in assessing abuse of discretion also creates legal uncertainty. The research recommends the need for a balance between the flexibility of discretion and effective control mechanisms, as well as clear parameters to distinguish between administrative and criminal abuses of discretion.